Good Will Hunting [videorecording (DVD)] - Van Sant, Gus; Williams, Robin, 1951-2014; Damon, Matt; Affleck, Ben, 1972- (Miramax Home Entertainment : Distributed by Buena Vista Home Entertainment, 1997)
A young working-class genius is hauled back from the brink of self-destruction by a gifted counselor.